2018
DOI: 10.1002/brb3.1111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired white matter integrity between premotor cortex and basal ganglia in writer’s cramp

Abstract: IntroductionWriter’s cramp (WC) as a focal hand dystonia is characterized by abnormal postures of the hand during writing. Impaired inhibition and maladaptive plasticity in circuits linking the basal ganglia and sensorimotor cortices have been described. In particular, a dysfunction of lateral premotor cortices has been associated with impaired motor control in WC. We applied diffusion tensor imaging to identify changes in white matter connectivity between premotor regions and important cortical and subcortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Brain γ-aminobutyric acid reductions as a potential correlate of impaired inhibitory projections have been observed both in the lentiform nucleus and in the primary sensorimotor cortex of the affected hemisphere in focal hand dystonia patients using magnetic resonance spectroscopy ( Levy and Hallett, 2002 ). While the significant cortico-subcortical tract abnormality reported in this work was confined to sensory trajectories, data in writer’s cramp similarly showed a reduction in axial diffusivity in the trajectory connecting the middle frontal gyrus and the putamen (together with fractional anisotropy) ( Berndt et al, 2018 ). This may indicate that other non-sensory cortices undergo comparable changes, though potential FD subtype-associated differences cannot be excluded ( Bianchi et al, 2019 , Ramdhani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 67%
“…Brain γ-aminobutyric acid reductions as a potential correlate of impaired inhibitory projections have been observed both in the lentiform nucleus and in the primary sensorimotor cortex of the affected hemisphere in focal hand dystonia patients using magnetic resonance spectroscopy ( Levy and Hallett, 2002 ). While the significant cortico-subcortical tract abnormality reported in this work was confined to sensory trajectories, data in writer’s cramp similarly showed a reduction in axial diffusivity in the trajectory connecting the middle frontal gyrus and the putamen (together with fractional anisotropy) ( Berndt et al, 2018 ). This may indicate that other non-sensory cortices undergo comparable changes, though potential FD subtype-associated differences cannot be excluded ( Bianchi et al, 2019 , Ramdhani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 67%
“… 81 , 82 , 83 , 84 Although overt demyelination has not been specifically documented in dystonia, neuroimaging studies have reported white matter abnormalities in multiple forms of the disease, including (1) syndromes associated with genetic variation in TOR1A , THAP1 , SGCE (MIM: 604149 , DYT11 [MIM: 159900 ]), TAF1 , KMT2B , and COL6A3 (MIM: 120250 , DYT27 [MIM: 616411 ]) 20 , 69 , 85 , 86 , 87 , 88 , 89 and (2) idiopathic cases of cervical dystonia, writer’s cramp, laryngeal dystonia, and blepharospasm. 90 , 91 , 92 , 93 The mechanisms underlying these disturbances in white matter tracts are not known, and further investigation is needed to determine whether they reflect common defects in any of the pathways perturbed by genetic variation in THAP1 .…”
Section: Discussionmentioning
confidence: 99%
“…[81][82][83][84] Although overt demyelination has not been specifically documented in dystonia, neuroimaging studies have reported white matter abnormalities in multiple forms of the disease, including: (1) syndromes associated with genetic variation in TOR1A, THAP1, SGCE, TAF1, KMT2B, and COL6A3 20,69,[85][86][87][88][89] ; and (2) idiopathic cases of cervical dystonia, writer's cramp, laryngeal dystonia, and blepharospasm. [90][91][92][93] The mechanisms underlying these disturbances in white matter tracts are not known, and further investigation is needed to determine if they reflect common defects in any of the pathways perturbed by genetic variation in THAP1.…”
Section: Discussionmentioning
confidence: 99%